PENINGKATAN HASIL BELAJAR SUBSTANSI GENETIKA MELALUI MODEL E-LEARNING DENGAN MEDIA MODUL DAN LKS BERGAMBAR PADA SISWA KELAS XII IPA-1 SMAN 1 BATANGHARI - JONI ALI (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2022)
CAR aims to find out that the E-Learning model through Google Classroom and WA Group, as well as Learning Modules and Picture Worksheets, can improve learning outcomes of Genetic Substances in class XII IPA-1 SMAN 1 Batanghari, totaling 27 people. The problems faced in the classroom are the low student learning activities, low learning achievement, and the difficulties (obstacles) in applying learning models, tools/facilities, methods, and media that are effective when used through electronic and online-based learning. Focus on the problem of improving learning outcomes of Genetic Substances in class XII IPA-1 SMAN 1 Batanghari. through the E-Learning model as well as learning modules and illustrated worksheets. The research was carried out in 2 cycles with the stages of planning, implementing, observing, and reflecting. The application of the GCR and WA Group applications (which are easily accessible and relatively inexpensive), as well as modules with illustrated worksheets (interesting and easily accessible learning media), effectively overcome obstacles and difficulties and increase learning activity and success compared to the models and learning media used previously. The results showed that by applying the E-Learning model through the GCR and WA Group applications, as well as learning module media and illustrated worksheets, it could increase the activeness and learning outcomes of Genetic Substances in class XII IPA-1 SMAN 1 Batanghari. ABSTRAKPTK bertujuan mengetahui bahwa dengan model E-Learning melalui Google Classroom dan WA Group, serta Modul Pembelajaran dan LKS Bergambar, dapat meningkatkan hasil belajar Substansi Genetika pada siswa kelas XII IPA-1 SMAN 1 Batanghari yang berjumlah 27 orang. Masalah yang dihadapi di kelas adalah rendahnya aktivitas belajar siswa, rendahnya prestasi belajar, dan adanya kesulitan (kendala) penerapan model pembelajaran, alat/sarana, metode, dan media yang efektif bila digunakan melalui pembelajaran berbasis eletronik dan daring. Focus masalah meningkatkan hasil belajar Substansi Genetika pada siswa kelas XII IPA-1 SMAN 1 Batanghari.melalui model E-Learning serta modul pembelajaran dan LKS bergambar. Penelitian dilaksanakan 2 siklus dengan tahapan kegiatan perencanaan, pelaksanaan, pengamatan/observasi, dan refleksi. Penerapan aplikasi GCR dan WA Group (yang mudah diakses dan relative murah), serta modul dengan LKS bergambar (media pembelajaran yang menarik dan mudah diakses), efektif mengatasi hambatan dan kesulitan serta meningkatkan keaktifan dan keberhasilan pembelajaran dibandingkan model dan media pembelajaran yang digunakan sebelumnya. Hasil penelitian menunjukkan bahwa dengan diterapkannya model E-Learning melalui aplikasi GCR dan WA Group, serta media modul pembelajaran dan LKS bergambar, dapat meningkatkan keaktifan dan hasil belajar Substansi Genetika pada siswa kelas XII IPA-1 SMAN 1 Batanghari.